Conductance of Water-sorbed Activated Carbon: Differentiation of Flow Direction - Badri, M.; Crouse, Karen Anne; M. Daud, Mohamed (1986)
The conductance of a piece of activated carbon immersed in water has been measured at several different temperatures. The upward and downward flow Qf water as well as the flow in the horizontal direction in the same piece was made possible by using various arrangements of the apparatus. The rate of increase in the conductance has been interpreted as the rate of flow of water into the pores of activated carbon.